2011
DOI: 10.1007/s12603-010-0304-6
|View full text |Cite
|
Sign up to set email alerts
|

What is associated with nutrition risk in very old age?

Abstract: Half the participants were at high nutrition risk. They tended to be widowed or live alone and had lower levels of haemoglobin and serum zinc. Those at lower nutrition risk had greater muscle mass and strength, lower body fat, consumed alcohol more frequently and engaged in more physical activity. Strategies which encourage older people to eat meals and be physically active with others may assist to improve their health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
46
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 23 publications
8
46
2
2
Order By: Relevance
“…A combination of at risk and high risk categories resulted in a prevalence of up to 62% (Southgate et al, 2010;Watson et al, 2010;Wham et al, 2011c). Living alone (McElnay et al, 2012;Ramage-Morin and Garriguet, 2013;Wham et al, 2011c), less social support (Ramage-Morin and Garriguet, 2013), depression (Ramage-Morin and Garriguet, 2013), poor self rated health (Wham et al, 2011a), disability (Wham et al, 2011a) and eating alone (Watson et al, 2010;Wham et al, 2011a) were identified as factors associated with malnutrition risk. Meanwhile, a higher mortality rate within 5 years was documented in the high nutritional risk group, compared to those in other groups (Broeska et al, 2013).…”
Section: Screen © IImentioning
confidence: 99%
See 2 more Smart Citations
“…A combination of at risk and high risk categories resulted in a prevalence of up to 62% (Southgate et al, 2010;Watson et al, 2010;Wham et al, 2011c). Living alone (McElnay et al, 2012;Ramage-Morin and Garriguet, 2013;Wham et al, 2011c), less social support (Ramage-Morin and Garriguet, 2013), depression (Ramage-Morin and Garriguet, 2013), poor self rated health (Wham et al, 2011a), disability (Wham et al, 2011a) and eating alone (Watson et al, 2010;Wham et al, 2011a) were identified as factors associated with malnutrition risk. Meanwhile, a higher mortality rate within 5 years was documented in the high nutritional risk group, compared to those in other groups (Broeska et al, 2013).…”
Section: Screen © IImentioning
confidence: 99%
“…SCREEN © II, an improved version of SCREEN © , identified 31-52% of individuals to be at high risk of malnutrition (Broeska et al, 2013;McElnay et al, 2012;Ramage-Morin and Garriguet, 2013;Wham et al, 2011a;Wham et al, 2011c). A combination of at risk and high risk categories resulted in a prevalence of up to 62% (Southgate et al, 2010;Watson et al, 2010;Wham et al, 2011c).…”
Section: Screen © IImentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research estimates 31-60% of the older NZ population to be at high nutrition risk. [9][10][11] Dietitians apply robust scientific knowledge about food and nutrition to promote optimal health outcomes to individuals, groups and communities in states of both health and disease. Dietitians are registered health professionals who meet standards required by the NZ Dietitians Board under the NZ Health Practitioners Competence Assurance Act (HPCA) 2003.…”
Section: What Gap This Fillsmentioning
confidence: 99%
“…Low food intake or consumption of compromised dietary variety by the elderly with poor appetite and difficulty in mastication may lead elderly more vulnerable to malnutrition and micronutrient deficiency. Such health disorders are further accentuated by social, psychological and physical factors [7][8][9]. Several studies have been conducted to address the overall nutritional status of elderly both in developed [10] as well developing countries [11][12][13].…”
Section: Introductionmentioning
confidence: 99%